2009
DOI: 10.1007/s00264-009-0844-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of the threaded Weill cup in primary total hip arthroplasty

Abstract: Uncemented, threaded acetabular components with smooth surface treatment were widely used in continental Europe in the 1970s and 1980s for primary total hip arthroplasty (THA). Previously published studies showed high failure rates in the mid-term. In a consecutive series of 116 patients, 127 threaded cups with smooth surface treatment (Weill cup; Zimmer, Winterthur, Switzerland) were implanted in combination with one type of uncemented stem. Patients were followed up clinically and radiographically. Mean time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…There have been concerns with early polyethylene wear and osteolysis with the first generation ABG cups [5] and also the threaded Weill and the Mercon cups [6], but Philippot et al [18] demonstrated good results using the dual articulation acetabular cup with 95% survival at 18 years, which is more consistent with our study with the Bicontact cup.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…There have been concerns with early polyethylene wear and osteolysis with the first generation ABG cups [5] and also the threaded Weill and the Mercon cups [6], but Philippot et al [18] demonstrated good results using the dual articulation acetabular cup with 95% survival at 18 years, which is more consistent with our study with the Bicontact cup.…”
Section: Discussionsupporting
confidence: 82%
“…The medium term results of the Bicontact total hip arthroplasty with a minimum follow-up of 6.5 years have been encouraging [4]. There are however concerns of osteolysis and loosening as a consequence of polyethylene particle wear [4][5][6] or early aseptic loosening due to reduced primary stability [1].…”
Section: Introductionmentioning
confidence: 95%
“…Although initial acetabular components were cemented, cementless acetabular components have gained popularity over the years and have become the primary components of choice in North America. This is despite the availability of ample literature supporting the use of cemented acetabular components [2][3][4][5][6] and suggesting a less optimal survivorship for cementless components [7][8][9][10][11][12][13][14] . However, there is a lack of long-term studies on the improved cementless implants that may have the potential for better survivorship and durability.…”
mentioning
confidence: 61%
“…In addition, when compared with other migration analysis studies using EBRA-FCA [9,19,38], our dropout rate was lower. We also recognize a possible bias because the acetabular components used in this cohort showed a high rate of aseptic loosening [7,8], as patients with cup loosening might reduce their activity which could influence wear and aseptic loosening of the stem; surgery for cup loosening also might have an influence on stem revision rate. Further, the migration threshold of 2.7 mm in this study using a single stem design might not apply to other stem designs, since such thresholds are almost certainly implant-specific.…”
Section: Discussionmentioning
confidence: 99%
“…However, prediction of longterm implant performance is difficult and definitive results regarding aseptic loosening are available only after lengthy followup [24,32,33]. Widespread use of poor-performing implants might occur before these results are available [7,8]. Therefore, reliable methods are needed to predict aseptic loosening and allow early evaluation of long-term implant performance during the first years after implantation.…”
Section: Introductionmentioning
confidence: 99%